1999
DOI: 10.1096/fasebj.13.8.823
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of filamentous actin inhibits human macrophage fusion

Abstract: The foreign body reaction to implanted biomaterials, characterized by the presence of macrophages and foreign body giant cells (FBGC), can result in structural and functional failure of the implant. Recently, we have shown that interleukin-4 and interleukin-13 can independently induce human macrophage fusion to form FBGC via a macrophage mannose receptor (MR) -mediated pathway. The MR is believed to mediate both endocytosis of glycoproteins and phagocytosis of microorganisms, which bear terminal mannose, fucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 45 publications
7
44
0
1
Order By: Relevance
“…Overall levels of F-actin were higher in M2 and micropatterned cells compared with unpatterned cells, although dramatic changes in cytoskeletal organization were not observed. Although such differences in the cytoskeleton with the macrophage polarization state have been previously reported (21), the functional role of actin in macrophages has been primarily associated with phagocytosis (22), podosome formation (23), or fusion events (24), and little is known about the role of the cytoskeleton in macrophage polarization. We found that abrogation of actin polymerization and actin/myosin contractility, as well as ROCK and MLCK activities, completely eliminated shape-induced effects on polarization, suggesting a critical role for actin in the modulation of macrophage polarization by cell shape.…”
Section: Discussionmentioning
confidence: 98%
“…Overall levels of F-actin were higher in M2 and micropatterned cells compared with unpatterned cells, although dramatic changes in cytoskeletal organization were not observed. Although such differences in the cytoskeleton with the macrophage polarization state have been previously reported (21), the functional role of actin in macrophages has been primarily associated with phagocytosis (22), podosome formation (23), or fusion events (24), and little is known about the role of the cytoskeleton in macrophage polarization. We found that abrogation of actin polymerization and actin/myosin contractility, as well as ROCK and MLCK activities, completely eliminated shape-induced effects on polarization, suggesting a critical role for actin in the modulation of macrophage polarization by cell shape.…”
Section: Discussionmentioning
confidence: 98%
“…The MR, expressed on some macrophages, epithelial, and endothelial cells (Takahashi et al 1998, Linehan et al 1999, is the prototype member of a family of multi-lectin receptors that recognize carbohydrates such as terminal mannose, fucose, N-acetylglucosamine, or glucose residues on the cell walls of infectious organisms (Stahl & Ezekowitz 1998). The MR is believed to mediate both endocytosis of glycoproteins and phagocytosis of micro-organisms or glucose residues (Astarie-Dequeker et al 1999, DeFife et al 1999, Lansink et al 1999. MR-mediated fusion occurs via a filamentous action-dependent pathway (DeFife et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The MR is believed to mediate both endocytosis of glycoproteins and phagocytosis of micro-organisms or glucose residues (Astarie-Dequeker et al 1999, DeFife et al 1999, Lansink et al 1999. MR-mediated fusion occurs via a filamentous action-dependent pathway (DeFife et al 1999). The MR is expressed on cells of the macrophage lineage, is not detectable on blood monocytes, and has its expression modulated by inflammatory mediators (Stein & Ezekowitz 1992).…”
Section: Discussionmentioning
confidence: 99%
“…13,16 In addition, similar to phagocytosis, actin polymerization and reorganization are observed during macrophage fusion and, when inhibited, prevent fusion and subsequent FBGC formation. 17 In the present study, we expanded on these observations by identifying lamellipodia formation as a key feature of the IL-4-induced cytoskeletal changes in macrophages. Consistent with the role of Rac1 in this process, we detected IL-4-induced Rac1 activation before changes in cell shape.…”
mentioning
confidence: 94%